Narrative in the feminine : Daphne Marlatt and Nicole Brossard - Knutson, Susan Lynne (CEL - Canadian Publishers Collection., 2000)
What does it mean to tell a story from a woman's point of view? How have Canadian Anglo/francophone writers translated feminist literary theory into practice? These and other questions are answered by these two avant-garde authors. It is also a study of two of their own important works.